Histone acetylation of glucose-induced thioredoxin-interacting protein gene expression in pancreatic islets. (December 2016) - Bompada, Pradeep; Atac, David; Luan, Cheng; Andersson, Robin; Omella, Judit Domènech; Laakso, Emilia Ottosson; Wright, Jason; Groop, Leif; De Marinis, Yang
Graphical abstract: Abstract: Thioredoxin-interacting protein (TXNIP) has been shown to be associated with glucose-induced deterioration of pancreatic beta cell function in diabetes. However, whether epigenetic mechanisms contribute to the regulation of TXNIP gene expression by glucose is not clear. Here we studied how glucose exerts its effect on TXNIP gene expression via modulation of histone acetylation marks. To achieve this, we applied clustered regularly interspaced short palindromic repeats/Cas9 (CRISPR/Cas9) to knock out histone acetyltransferase (HAT) p300 in a rat pancreatic beta cell line INS1 832/13. We also treated the cells and human islets with chemical inhibitors of HAT p300 and histone deacetylase (HDAC). In human islets, diabetes and high glucose resulted in elevated TXNIP and EP300 expression, and glucose-induced TXNIP expression could be reversed by p300 inhibitor C646. In INS1 832/13 cells, Ep300 knock-out by CRISPR/Cas9 elevated glucose-induced insulin secretion and greatly reduced glucose-stimulated Txnip expression and cell apoptosis. This effect could be ascribed to decrease in histone marks H3K9ac and H4ac at the promoter and first coding region of the Txnip gene. Histone marks H3K9ac and H4ac in the Txnip gene in the wild-type cells was inhibited by HDAC inhibitor at high glucose, which most likely was due to enhanced acetylation levels of p300 after HDAC inhibition; and thereby reduced p300 binding to the Txnip gene promoter region. Such inhibition was absent in the Ep300 knock-out cells. Our study provides evidence that histone acetylation serves as a key regulator of glucose-induced increase in TXNIP gene expression and thereby glucotoxicity-induced apoptosis.